Microfluidic Cell Trap Arrays for Single Hematopoietic Stem/ Progenitor Cell Behavior Analysis - Han, Xin (Proteomics, 2020)
Hematopoietic stem/progenitor cell (HSPC) mobilization from the bone marrow to the bloodstream is a required step for blood cell renewal and HSPC motility is a clinically relevant standard for peripheral blood stem cell transplantation. Individual HSPCs exhibit considerable heterogeneity in motility behaviors, which are subject to complex intrinsic and extrinsic regulatory mechanisms. Motility based cell sorting is then demanded to fulfill the study of such mechanism complexity. However, due to the HSPC heterogeneity and difficulty in monitoring cell motility, such a platform is still not available. With the recent development of microfluidics technology, motility-based monitoring, sorting, collecting, and analysis of HSPCs behaviors are highly possible and achievable if fluid channels and structures are correctly engineered. Here, we present a new design of microfluidic arrays for single-cell trapping, enabling high-throughput analysis of individual HSPC motility and behavior. Using these arrays, we observe that HSPC motility is positively correlated with CD34 asymmetric inheritance and cell differentiation. Transcriptomic analysis of HSPCs sorted according to motility reveals changes in expression of genes associated with the regulation of stem-cell maintenance. Ultimately, our novel physical cell-sorting system can facilitate the screening of HSPC mobilization compounds and the analysis of signals driving HSPC fate decisions.